The Mouse Island Marathon - Stilton, Geronimo (New York : Scholastic, 2007)
Geronimo Stilton is entered in the Mouse Island Marathon by his friend Champ Strongpaws who then forces him to train for it.
Includes "Champ's top ten tips for becoming a supermouse!"
"English translation...by Edizioni Piemme S.p.A."--T.p. verso.
Keywords: Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; Marathon running -- Juvenile fiction; Mice -- Fiction; Marathon running -- Fiction; Journalists -- Fiction; Humorous stories